'Real Bahamians' and 'paper Bahamians': Haitians as perpetual foreigners. Issue 1 (2nd January 2023) - Perry, Charmane M.
ABSTRACT: In the Bahamas, children born to undocumented migrants grow up without citizenship but are entitled to apply for it upon their eighteenth birthday. However, due to the stigma of having Haitian origin, Bahamians of Haitian descent continue to be othered racially and ethnically even after eventually becoming Bahamian citizens. In this essay, I argue that second-generation Haitian Bahamians are viewed as perpetual foreigners by mainstream Bahamians and continuously struggle to access the benefits of cultural and legal Bahamian citizenship. Structural and individual practices of 'othering' and exclusion have created notions of a two-tier system of citizenship in the Bahamas where some people are considered to be 'real Bahamians' and others are considered to be 'paper Bahamians.' Using semi-structured interviews with second-generation Haitian Bahamians with and without citizenship, participants reveal the ways they continue – or expect to continue – to experience discrimination and exclusion from Bahamian citizenship because of their Haitian ethnicity. Second-generation Haitians are often treated as perpetual foreigners and practices of individual and structural discrimination reproduce inequality and reflect the failure to fully integrate Haitians into Bahamian society.